2022
DOI: 10.1172/jci156290
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise GATA1 and SMC3 mutations alter megakaryocyte differentiation in a Down syndrome leukemia model

Abstract: Acute megakaryoblastic leukemia of Down syndrome (DS-AMKL) is a model of clonal evolution from a preleukemic transient myeloproliferative disorder requiring both a trisomy 21 (T21) and a GATA1 s mutation to a leukemia driven by additional driver mutations. We modeled the megakaryocyte differentiation defect through stepwise gene editing of GATA1s , SMC3 +/– , and MPL W515K , providing 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…37 In contrast, the 12 RUNX1A-specific cofactors were involved in active transcription/replication and G1-S transition, including the megakaryocytic transcription factor NFE2, which is mutated in a subset of patients with myeloid neoplasms and is functionally involved in the megakaryocyte differentiation blockage of GATA1s pluripotent stem cells (Figure 4B). [38][39][40] Importantly, MAX, a crucial cofactor of MYC, was among the RUNX1Aspecific interacting proteins, as verified via western blot (Figure 4C). GATA1s coimmunoprecipitated with RUNX1A and RUNX1C, albeit not at a significant enrichment level (data not shown).…”
Section: Distinct Runx1a and Runx1c Protein Interaction Networkmentioning
confidence: 63%
“…37 In contrast, the 12 RUNX1A-specific cofactors were involved in active transcription/replication and G1-S transition, including the megakaryocytic transcription factor NFE2, which is mutated in a subset of patients with myeloid neoplasms and is functionally involved in the megakaryocyte differentiation blockage of GATA1s pluripotent stem cells (Figure 4B). [38][39][40] Importantly, MAX, a crucial cofactor of MYC, was among the RUNX1Aspecific interacting proteins, as verified via western blot (Figure 4C). GATA1s coimmunoprecipitated with RUNX1A and RUNX1C, albeit not at a significant enrichment level (data not shown).…”
Section: Distinct Runx1a and Runx1c Protein Interaction Networkmentioning
confidence: 63%
“…GATA1s mutation alone disrupts differentiation of megakaryocytes and promotes expansion of myeloid and megakaryocytic progenitors, while production of aberrant megakaryoblasts is strengthened on the background of trisomy 21 ( Banno et al, 2016 ; Juban et al, 2021 ; Matsuo et al, 2021 ). TAM requires the synergy between trisomy 21 and GATA1s but leukemic transformation may be independent of trisomy 21 ( Wagenblast et al, 2021 ; Arkoun et al, 2022 ). In contrast, synergy between GATA1s and subsequent “tertiary” molecular alterations is critical for progression of TAM to ML-DS.…”
Section: Gata1 Mutationsmentioning
confidence: 99%
“…GATA1s and STAG2 knockout cooperatively increased the megakaryocytic population and induced the ML-DS immunophenotype ( Barwe et al, 2022 ). In another study, trisomic 21 iPSC line ( Chou et al, 2012 ) was edited to introduce GATA1s followed by heterozygous inactivation of SMC3 ( SMC3 +/− ) and then, introduction of a gain-of-function MPL mutation (MPLW515K) ( Arkoun et al, 2022 ). It was found that GATA1s impaired megakaryocyte differentiation and that SMC3 +/− enhanced this effect independent of trisomy 21.…”
Section: Tertiary Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To help understand the evolution of TMD to DS-AMKL, it is necessary to develop human-relevant models that can recapitulate the DS-AMKL mutations and allow examination of progressive perturbations of megakaryocytic differentiation and other disease phenotypes. In this issue of the JCI , Arkoun and colleagues accomplish this objective using a stepwise technique to introduce GATA1 , MPL , and SMC3 mutants into induced pluripotent stem cells (iPSCs) from humans with or without DS ( 9 ). The researchers uncovered the individual contributions of each variant and how they could cooperate with T21 to lead to DS-AMKL.…”
Section: Acute Megakaryoblastic Leukemia Of Down Syndromementioning
confidence: 99%